Polarized training has greater impact on key endurance variables than threshold, high intensity,or high volume training - Stöggl, T.; Sperlich, B. (Frontiers in Physiology, 2014)
Endurance athletes integrate four conditioning concepts in their training programs: high-volume training (HVT), "threshold-training" (THR), high-intensity interval training (HIIT) and a combination of these aforementioned concepts known as polarized training (POL). The purpose of this study was to explore which of these four training concepts provides the greatest response on key components of endurance performance in well-trained endurance athletes.